Nano carboxymethyl cellulose salt and preparation method thereof, binder, pole piece and battery
By preparing nanocarboxymethylcellulose salt and applying it to the battery electrode adhesive, the problem that sodium carboxymethylcellulose in the battery in the prior art cannot meet the high cycle performance and rate performance, and the high electrode plate is achieved The strength and low resistivity significantly improve the battery's cycling and rate performance.
Patent Information
- Application Number
- CN202411725311.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-21
AI Technical Summary
The existing sodium carboxymethylcellulose cannot effectively achieve high cycling performance and rate performance in the battery, resulting in expansion, powder loss and increased resistivity of the pole sheet during the cycle.
By preparing nanocarboxymethylcellulose salts, using specific catalysts and treatment steps, including alkalization and etherification treatment, nanocarboxymethylcellulose salts with excellent esterification and carboxylation, and applying them to the in the pole adhesive of the battery.
The high strength, low expansion, low powder loss and low resistivity of the pole sheet are achieved, which significantly improves the cycle performance and rate performance of the battery.
Smart Images

Figure CN119490604A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a nano carboxymethyl cellulose salt and a preparation method thereof, a binder, a pole piece and a battery. Background Art
[0002] Nowadays, the 3C consumer battery field is increasingly inclined to develop in the direction of high energy density, which has led to the rapid development of silicon-carbon negative electrodes. Compared with traditional graphite materials, today's silicon-carbon negative electrode materials are prone to expansion during the lithium insertion process. Although the new silane-precipitated silicon-carbon can greatly alleviate its expansion, according to current performance, the conventional formula of silicon-carbon negative electrode, when the silicon-carbon doping amount is 10% and the compaction density is 1.73g / cm 3 When the electrode is used for a long time, the expansion of the electrode is about 100%. The huge volume expansion makes the active substances on the surface of the current collector easy to fall off during the long-term cycle, so it is imperative to develop a new type of binder.
[0003] Sodium carboxymethyl cellulose is an indispensable binder for silicon-carbon negative electrode materials, but the existing sodium carboxymethyl cellulose cannot effectively stabilize the slurry, keep it from settling for a long time, improve the viscosity for stable coating, reduce the probability of bubble generation in the electrode, reduce powder loss on the surface of the negative electrode, increase the toughness of the negative electrode, and enhance the wettability of the electrode by electrolyte, so that the existing sodium carboxymethyl cellulose cannot meet the high cycle performance and rate performance when used in batteries. Summary of the invention
[0004] In order to solve the problem that sodium carboxymethyl cellulose in the prior art cannot meet high cycle performance and high rate performance when used in batteries, the present invention provides a nano carboxymethyl cellulose salt and a preparation method thereof, a binder, a pole piece and a battery. The nano carboxymethyl cellulose salt can have both high cycle performance and high rate performance when used in batteries.
[0005] To achieve the above objectives, the present invention adopts the following technical solutions.
[0006] The present invention provides a method for preparing nano carboxymethyl cellulose salt, which comprises the following steps:
[0007] The cellulose raw material and the mixture are reacted to obtain a precipitate; the precipitate is sequentially subjected to an alkalization treatment and an etherification treatment to obtain the nano carboxymethyl cellulose salt; wherein the mixture comprises a first catalyst and a second catalyst, the first catalyst is a catalyst having a function of catalyzing an esterification reaction, and the second catalyst is an acid solution.
[0008] In the present invention, the cellulose raw material may be a conventional cellulose-containing material in the art, such as one or more of wood, straw, pulp and cotton, preferably cotton.
[0009] In the present invention, the cellulose content in the cellulose raw material is preferably 90% or more, more preferably 95% or more, for example 99.5% or 99.9%.
[0010] In the present invention, the ash content of the cellulose raw material is preferably less than 10%, more preferably less than 5%, and further more preferably less than 0.1%, for example, 0.1%. In the present invention, setting the ash content to less than 10% can further improve the crystallinity and strength of the nano-carboxymethyl cellulose salt, and can reduce the negative impact between it and the electrolyte.
[0011] In the present invention, preferably, the first catalyst comprises one or more of pyridine compounds, pyrimidine compounds and pyrrole compounds, wherein the pyridine compounds are pyridine and its derivatives, the pyrimidine compounds are pyrimidine and its derivatives, and the pyrrole compounds are pyrrole and its derivatives.
[0012] Wherein, the pyridine compound is preferably 4-dimethylaminopyridine (DMAP) and / or 4-phenylaminopyridine, preferably 4-dimethylaminopyridine.
[0013] In the present invention, the acid solution is preferably sulfuric acid and / or phosphoric acid, preferably sulfuric acid.
[0014] Wherein, the mass concentration of the sulfuric acid is preferably 5%-15%, for example, 10%.
[0015] In the present invention, the mass ratio of the cellulose raw material to the first catalyst is preferably (5-50):1, for example, 5:1, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1 or 45:1, preferably 20:1.
[0016] In the present invention, the mass ratio of the cellulose raw material to the second catalyst is preferably 1:(1-50), for example, 1:5, 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40 or 1:45, preferably 1:10.
[0017] In the present invention, the reaction temperature is preferably -20~100°C, for example, -20°C, 0°C, 5°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C or 100°C, preferably 60°C.
[0018] In the present invention, the reaction time is preferably 1-10 h, more preferably 2-9 h, for example 3 h, 4 h, 5 h, 6 h, 7 h or 8 h, further more preferably 2-4 h, preferably 3 h.
[0019] In the present invention, the maximum particle size of the precipitate is preferably 0.1-2 μm, for example, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.8 μm, 1 μm, 1.2 μm, 1.4 μm, 1.6 μm or 1.8 μm. The maximum particle size of the precipitate in the present invention is in the range of 0.1-2 μm. On the one hand, it can play a skeleton role, enabling the nano carboxymethyl cellulose salt to be used in the slurry and the pole piece, further improve the pole piece strength, inhibit expansion, prevent cracking, enhance wettability and improve the stability of the slurry. On the other hand, it can avoid agglomeration, improve the dispersibility of the slurry, and at the same time improve the esterification degree of the nano carboxymethyl cellulose salt, thereby improving the rate performance of the pole piece.
[0020] In certain specific embodiments of the present invention, the following steps are further included after the reaction to obtain a precipitate: deionized water is added to the product after the reaction, and the precipitate is separated after standing.
[0021] The standing time is, for example, 24 hours.
[0022] The separation is carried out by centrifugation, for example, wherein the rotation speed of the centrifuge is, for example, 4000 r / min.
[0023] In the present invention, the pH value of the precipitate is preferably 6-10, for example, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, preferably 7.5.
[0024] In some specific embodiments of the present invention, the pH value of the precipitate is adjusted by aqueous ammonia.
[0025] In the present invention, preferably, the alkalization treatment step comprises: mixing an alkalizer and a dispersion containing precipitates for alkalization treatment.
[0026] Preferably, the alkalizing agent is sodium hydroxide.
[0027] Preferably, the mass ratio of the precipitate to the alkalizing agent is (2-10):1, for example, 5:1.
[0028] Wherein, after the alkalizing agent and the dispersion containing the precipitate are mixed, the pH value of the dispersion containing the precipitate is preferably 8-14, for example, 9, 10, 11, 12 or 13.
[0029] The alkalization step preferably comprises: mixing the alkalizer, the dispersion containing the precipitate and ethanol and then performing alkalization. The addition of ethanol can accelerate the wetting effect of sodium hydroxide and promote the degree of alkalization.
[0030] The mass concentration of the ethanol is, for example, 75%.
[0031] The mass ratio of the alkalizing agent to the volume ratio of the ethanol is, for example, 20:1, wherein the unit of mass is g and the unit of volume is L.
[0032] In certain specific embodiments of the present invention, the mass ratio of the dispersion containing the precipitate to the alkalizing agent is preferably (1-1000):1, for example, 5:1, 10:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, 100:1, 200:1, 300:1, 400:1, 500:1, 600:1, 700:1, 800:1 or 900:1.
[0033] Preferably, the temperature of the alkalization treatment is below 35°C, for example 35°C.
[0034] Preferably, the alkalization treatment time is 0.5-4 h, for example, 1 h, 2 h or 3 h.
[0035] The method for preparing the dispersion containing the precipitate preferably comprises: mixing a dispersant and the precipitate to form the dispersion containing the precipitate.
[0036] Preferably, the solid content of the dispersion containing the precipitate is 0.01%-20%, for example, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18% or 19%, for example, 5%. The solid content means the mass percentage of the precipitate in the dispersion to the mass percentage of the dispersion.
[0037] Wherein, the dispersant is preferably ethanol.
[0038] Among them, in the preparation method of the dispersion containing precipitate, the mixing includes a first mixing and a second mixing in sequence. After the first mixing, in the dispersion containing precipitate, the mass ratio of the precipitate to the dispersant is 1:99.
[0039] Wherein, the second mixing is preferably performed by ultrasonic treatment.
[0040] The ultrasonic treatment time is, for example, 30 minutes.
[0041] Wherein, the ultrasonic treatment is preferably performed using an ultrasonic cell disruptor.
[0042] Preferably, the ultrasonic treatment further includes centrifugal treatment.
[0043] The centrifugal speed of the centrifugal treatment is, for example, 14000 r / min.
[0044] In the present invention, preferably, the etherification treatment step comprises: mixing an etherifying agent and a treatment liquid containing precipitates and then heating the mixture for etherification treatment; the treatment liquid containing precipitates is obtained after the alkalization treatment.
[0045] Preferably, the heating includes first heating and second heating in sequence, the temperature of the first heating is 40-70°C; the temperature of the second heating is 60-90°C.
[0046] The first heating temperature is, for example, 45°C, 50°C, 55°C, 60°C or 65°C.
[0047] The second heating temperature is, for example, 65°C, 70°C, 75°C, 80°C or 85°C.
[0048] The first heating time is preferably 30-60 min, for example, 35 min, 40 min, 45 min, 50 min or 55 min.
[0049] The second heating time is preferably 0.5-10 h, for example, 1 h, 1.5 h, 2.0 h or 5 h.
[0050] The heating is, for example, water bath reflux heating.
[0051] In the present invention, preferably, the etherifying agent comprises chloroacetic acid.
[0052] Preferably, the etherifying agent also includes ethanol.
[0053] Preferably, the mass content of chloroacetic acid in the etherifying agent is 20%-30%, for example, 26%, wherein % means the mass of chloroacetic acid as a percentage of the mass of the etherifying agent.
[0054] Preferably, the mass ratio of the precipitate to the chloroacetic acid is 1:(0.05-0.1), for example, 1:0.057.
[0055] In certain specific embodiments of the present invention, the mass ratio of the treatment liquid containing the precipitate to the volume ratio of the etherifying agent is preferably 1:(5-100), for example, 1:10, 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80 or 1:90, wherein the unit of mass is kg and the unit of volume is mL.
[0056] In the present invention, preferably, the etherification treatment further includes a step of removing impurities.
[0057] The impurity removal is performed by, for example, dialysis.
[0058] Wherein, the molecular cutoff of the dialysis bag used for dialysis is 8000-14000.
[0059] In some specific embodiments of the present invention, the pH value of the nano carboxymethyl cellulose salt is 7-8, for example, 7.7.
[0060] In the present invention, preferably, the nano carboxymethyl cellulose salt is nano carboxymethyl cellulose sodium.
[0061] The invention also provides a nano carboxymethyl cellulose salt prepared by the preparation method of the nano carboxymethyl cellulose salt.
[0062] In the present invention, the shape of the crystal particles of the nano-carboxymethyl cellulose salt can be linear.
[0063] In the present invention, the average length of the crystal particles of the nano-carboxymethyl cellulose salt may be 200-400 nm, preferably 200-350 nm, for example 250 nm, 270 nm, 300 nm or 320 nm.
[0064] In the present invention, the surface charge of the nano carboxymethyl cellulose salt can be -40 to -60 mV, for example, -56 mV, -54 mV, -53 mV or -44 mV. The surface charge can characterize the degree of esterification of the nano carboxymethyl cellulose salt, wherein the greater the charge amount of the surface charge, that is, the lower the value of the surface charge, the higher the degree of esterification.
[0065] In the present invention, the degree of substitution of the nano carboxymethyl cellulose salt may be 1-3, for example, 1.1 or 1.2.
[0066] In the present invention, the nano carboxymethyl cellulose salt may be nano carboxymethyl cellulose sodium.
[0067] In the present invention, the crystallinity of the nano-carboxymethyl cellulose salt may be 70%-90%, for example, 80.4%, 83.3%, 83.4% or 83.5%.
[0068] In the present invention, the strength of the nano carboxymethyl cellulose salt may be 110-135 MPa, for example, 112.7 MPa, 121.3 MPa, 125.5 MPa or 126.3 MPa.
[0069] The invention also provides a binder, which comprises the nano carboxymethyl cellulose salt.
[0070] In the present invention, preferably, the mass percentage of the nano-carboxymethyl cellulose salt to the mass percentage of the binder is 6%-25%, for example, 12%, 17% or 21%.
[0071] In the present invention, preferably, the binder further comprises polyacrylic acid (PAA) and / or styrene-butadiene rubber (SBR).
[0072] Preferably, the mass of the polyacrylic acid accounts for 60%-80% of the mass of the binder, for example, 63%, 66%, 69%, 74% or 78%.
[0073] Preferably, the mass of the styrene-butadiene rubber accounts for 10%-20% of the mass of the adhesive, for example, 13%, 14%, 15% or 16%.
[0074] The present invention also provides a pole piece, which comprises a current collector and an active material layer, wherein the active material layer comprises the above-mentioned binder.
[0075] In the present invention, the electrode sheet is preferably a negative electrode sheet.
[0076] In the present invention, preferably, the mass of the binder accounts for 3%-4% of the mass of the active material layer, for example, 3.2%, 3.4%, 3.6% or 3.8%.
[0077] In the present invention, preferably, the mass percentage of the nano-carboxymethyl cellulose salt to the mass percentage of the active material layer is 0.2%-1%, more preferably 0.4%-1%, for example 0.6% or 0.8%.
[0078] In the present invention, preferably, the mass of the polyacrylic acid accounts for 2%-3% of the mass of the active material layer, for example, 2.5%.
[0079] In the present invention, preferably, the mass of the styrene-butadiene rubber accounts for 0.2%-1% of the mass of the active material layer, for example, 0.5%.
[0080] In the present invention, preferably, the active material layer further includes a negative electrode active material.
[0081] The negative electrode active material preferably includes one or more of conductive carbon black (SP), carbon nanotubes (CNTs), silicon-carbon material and conductive graphite.
[0082] Preferably, the mass percentage of the negative electrode active material in the active material layer is 96%-97%, for example, 96.2%, 96.4%, 96.6% or 96.8%.
[0083] In certain specific embodiments of the present invention, the electrode sheet may be prepared in a conventional manner in the art, for example, by coating a negative electrode slurry on a current collector and baking the negative electrode slurry to form the active material layer; the negative electrode slurry includes the binder.
[0084] In a specific embodiment of the present invention, the baking temperature is 80°C.
[0085] In a specific embodiment of the present invention, the baking time is 400s.
[0086] In a specific embodiment of the present invention, the coating speed is 40 cm / s.
[0087] In a specific embodiment of the present invention, the current collector is copper foil.
[0088] In a specific embodiment of the present invention, the thickness of the copper foil is, for example, 8 μm.
[0089] In a specific embodiment of the present invention, the preparation method of the negative electrode slurry includes: mixing graphite, nano-sodium carboxymethyl cellulose, SP, and CNTs in a stirring tank, dispersing them for 3 hours with a planetary disperser at a rotation speed of 300 r / min and a revolution speed of 1000 r / min, injecting 80% deionized water at a speed of 500 r / min and a revolution speed of 600 r / min for 1 hour, adding PAA at a rotation speed of 500 r / min and a revolution speed of 500 r / min for 1 hour, and finally adding SBR at a rotation speed of 300 r / min and a revolution speed of 300 r / min for 1 hour to form a negative electrode slurry.
[0090] The present invention also provides a battery, which comprises the above-mentioned pole piece.
[0091] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0092] The reagents and raw materials used in the present invention are commercially available.
[0093] The positive and progressive effects of the present invention are:
[0094] The crystal grains of the nano carboxymethyl cellulose salt prepared by the present invention are linear in shape, have excellent esterification degree and carboxylation degree, and when applied to the binder of the pole piece, can increase its bonding effect and improve the tap density. The pole piece has low pole piece powder loss, low expansion amount, low expansion ratio, low resistivity and high pole piece peeling force; when applied to a battery, can improve the cycle performance and rate performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0095] Figure 1This is the TEM image of the nano-sodium carboxymethyl cellulose prepared in Example 1. DETAILED DESCRIPTION
[0096] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0097] Preparation of Nano-carboxymethylcellulose Salt:
[0098] Example 1
[0099] The preparation method of nano sodium carboxymethyl cellulose comprises the following steps:
[0100] S1, reacting 1 kg of cellulose raw material and the mixture to obtain a product, adding 20 kg of deionized water to the product and letting it stand for 24 hours, centrifuging at a speed of 4000 r / min, and adjusting the pH value of the obtained precipitate to 7.5 with ammonia water;
[0101] The cellulose raw material is cotton with a cellulose content of 99.9% and an ash content of 0.1%; the mixture includes a first catalyst and a second catalyst, the first catalyst is 4-dimethylaminopyridine (DMAP), and the second catalyst is sulfuric acid with a mass concentration of 10%; the mass ratio of the cellulose raw material to the first catalyst is 20:1, and the mass ratio of the cellulose raw material to the second catalyst is 1:10.
[0102] The reaction temperature was 60°C and the reaction time was 3 hours. The maximum particle size of the obtained precipitate was 0.3 μm.
[0103] S2. The dispersant ethanol and the above-mentioned precipitate are subjected to a first mixing, a second mixing and a centrifugal treatment in sequence to form a 4 kg dispersion containing precipitate with a solid content of 5%; after the first mixing, the mass ratio of the precipitate to the dispersant in the dispersion containing the precipitate is 1:99; the second mixing is carried out by ultrasonic treatment with an ultrasonic cell crusher for 30 minutes; the centrifugal speed of the centrifugal treatment is 14000r / min.
[0104] S3. Add 40 g of sodium hydroxide alkalizer (the mass ratio of precipitate to alkalizer is 5:1) to 4 kg of the above-mentioned dispersion containing precipitate to adjust the pH value of the dispersion containing precipitate to 14, and add 2000 mL of ethanol with a mass concentration of 75% for alkalization treatment. The alkalization treatment temperature is 35° C. and the alkalization treatment time is 1 hour. After the alkalization treatment, a treatment liquid containing precipitate is formed.
[0105] S4, after mixing 40mL of the etherifying agent and the above-mentioned treatment solution containing the precipitate, perform a first heating and a second heating in sequence, the first heating is heating in a water bath under reflux at 55°C for 45min, and the second heating is heating in a water bath under reflux at 70°C for 1.5h; after the end, remove impurities with a dialysis bag with a molecular cutoff of 8000-14000, and obtain nano sodium carboxymethyl cellulose with a pH value of 7.7 after the removal of impurities;
[0106] The etherifying agent includes chloroacetic acid and ethanol, the mass content of chloroacetic acid in the etherifying agent is 26%, and the mass ratio of the precipitate to chloroacetic acid is 1:0.057.
[0107] Example 2
[0108] The preparation method of nano sodium carboxymethyl cellulose in Example 2 comprises the following steps: the first catalyst added in S1 is 4-phenylaminopyridine, and the other steps are the same as those in Example 1.
[0109] Example 3
[0110] The preparation method of nano sodium carboxymethyl cellulose in Example 3 comprises the following steps: in S1, the mass ratio of the cellulose raw material to the first catalyst is 40:1, and the other steps are the same as those in Example 1.
[0111] Example 4
[0112] The preparation method of nano sodium carboxymethyl cellulose in Example 4 comprises the following steps: in S1, the mass ratio of the cellulose raw material to the second catalyst is 1:30, and the other steps are the same as those in Example 1.
[0113] Preparation of pole piece:
[0114] Example 5
[0115] The formula of the negative electrode slurry is: by mass ratio, binder: SP: CNTs: silicon carbon: conductive graphite = 4:1:0.1:8:86.9, and the rest is solvent deionized water.
[0116] The binder includes the nano-sodium carboxymethyl cellulose, PAA and SBR prepared in Example 1, and the mass percentage of each component in the negative electrode slurry is 1%, 2.5% and 0.5% respectively.
[0117] The specific preparation process of the negative electrode slurry is as follows: after mixing graphite, nano-sodium carboxymethyl cellulose, SP, and CNTs in a stirring tank, disperse them for 3 hours with a planetary disperser at a rotation speed of 300r / min and a revolution speed of 1000r / min, inject 80% deionized water at a speed of 500r / min and a revolution speed of 600r / min for 1 hour, add PAA and disperse it at a rotation speed of 500r / min and a revolution speed of 500r / min for 1 hour, and finally add SBR and disperse it at a rotation speed of 300r / min and a revolution speed of 300r / min for 1 hour to form a negative electrode slurry.
[0118] Preparation process of negative electrode sheet: The above negative electrode slurry is coated on one side of 8μm thick copper foil, with the coated side facing the negative electrode of button battery. The thickness of active material coated on one side is 40μm, and the compaction density is 1.7g / cm 3 , wherein the coating speed is 40 cm / s, the baking temperature is 80°C, and the baking time is 400s.
[0119] After baking, the deionized water evaporates and the negative electrode slurry forms an active material layer. In the active material layer, the mass ratio of binder: SP: CNTs: silicon carbon: conductive graphite is 4:1:0.1:8:86.9.
[0120] Example 6 to Example 12
[0121] The binder formulations of Examples 6 to 9 are listed in the table below, wherein the nano-carboxymethyl cellulose of Examples 6-9 adopts the nano-carboxymethyl cellulose prepared in Example 1, the nano-carboxymethyl cellulose of Example 10 adopts the nano-carboxymethyl cellulose prepared in Example 2, the nano-carboxymethyl cellulose of Example 11 adopts the nano-carboxymethyl cellulose prepared in Example 3, and the nano-carboxymethyl cellulose of Example 12 adopts the nano-carboxymethyl cellulose prepared in Example 4. The rest of the process for preparing the negative electrode sheet is the same as that of Example 1.
[0122] Comparative Examples 1-10
[0123] Comparative Examples 1-7 and Comparative Example 10
[0124] The negative electrode slurries of Comparative Examples 1-4 and Comparative Example 10 do not contain sodium carboxymethyl cellulose.
[0125] The sodium carboxymethyl cellulose in Comparative Examples 5-7 all uses commercially available absorbent cotton, the manufacturer of which is Nippon Paper Industry, the model is MAC350HC, the length of the crystal is 42 μm, the degree of substitution is 0.81, and it has not been esterified.
[0126] The negative electrode slurries of Comparative Examples 1-7 and Comparative Example 10 are the same as those of Example 5 except for the differences listed in Table 1 below. The preparation methods of the negative electrode slurries and negative electrode sheets are also the same as those of Example 5.
[0127] Comparative Example 8
[0128] The preparation method of sodium carboxymethyl cellulose in Comparative Example 8 comprises the following steps: in S1, the first catalyst 4-dimethylaminopyridine is not added, an equal amount of deionized water is used, and the remaining steps are the same as those in Example 1.
[0129] The formula of the negative electrode slurry of Comparative Example 8 is the same as that of Example 5 except for the differences listed in the following table. The preparation method of the negative electrode slurry and the negative electrode sheet is also the same as that of Example 5.
[0130] Comparative Example 9
[0131] The preparation method of sodium carboxymethyl cellulose in Comparative Example 9 comprises the following steps: in S1, no second catalyst sulfuric acid is added, an equal amount of deionized water is used, and the remaining steps are the same as those in Example 1.
[0132] The formula of the negative electrode slurry of Comparative Example 9 is the same as that of Example 5 except for the differences listed in the following table. The preparation method of the negative electrode slurry and the negative electrode sheet is also the same as that of Example 5.
[0133] Table 1
[0134] Source of Sodium Carboxymethyl Cellulose The mass percentage of sodium carboxymethyl cellulose in the active material layer The mass percentage of PAA in the active material layer Mass percentage of SBR in the active material layer The mass percentage of conductive graphite in the active material layer Example 5 Example 1 Preparation 1% 2.5% 0.5% 86.9% Example 6 Example 1 Preparation 0.8% 2.5% 0.5% 87.1% Example 7 Example 1 Preparation 0.6% 2.5% 0.5% 87.3% Example 8 Example 1 Preparation 0.4% 2.5% 0.5% 87.5% Example 9 Example 1 Preparation 0.2% 2.5% 0.5% 87.7% Example 10 Example 2 Preparation 1% 2.5% 0.5% 86.9% Embodiment 11 Example 3 1% 2.5% 0.5% 86.9% Example 12 Example 4 Preparation 1% 2.5% 0.5% 86.9% Comparative Example 1 / 0 3.5% 0.5% 86.9% Comparative Example 2 / 0 3% 1% 86.9% Comparative Example 3 / 0 2.5% 1.5% 86.9% Comparative Example 4 / 0 2% 2% 86.9% Comparative Example 5 Commercially available products 0.5% 2.5% 1% 86.9% Comparative Example 6 Commercially available products 1% 2.5% 0.5% 86.9% Comparative Example 7 Commercially available products 1.5% 2.5% 0 86.9% Comparative Example 8 Comparative Example 8 1% 2.5% 0.5% 86.9% Comparative Example 9 Comparative Example 9 1% 2.5% 0.5% 86.9% Comparative Example 10 / 0 2.5% 0.5% 87.9%
[0135] Note: “ / ” in the table means not included.
[0136] Effect Example 1
[0137] The shape of the nano-carboxymethyl cellulose sodium crystals obtained in Example 1-Example 4 is linear. The nano-carboxymethyl cellulose sodium prepared in Example 1-Example 4 and Comparative Examples 8-9 was subjected to the following tests:
[0138] 1. Substitution degree test: Use 0.1mol / L H2SO4 standard solution for titration, accurately record the volume of H2SO4 standard solution consumed, and calculate the substitution degree DS according to the following formula: DS=0.162B / (1-0.08B); where B=2cV / m;
[0139] Among them, B (mmol / g) is the amount of sodium carboxymethyl contained in each gram of sample; 0.162mmol is the amount of one dehydrated glucose unit in cellulose; 0.08mmol is the increased amount of introduced sodium carboxymethyl group; c (mol / L) is the molar concentration of H2SO4 standard solution; V (mL) is the volume of H2SO4 standard solution consumed; m (g) is the mass of the prepared nano sodium carboxymethyl cellulose (CMC-Na) sample.
[0140] Among them, the degree of substitution can characterize the degree of carboxylation of nano-sodium carboxymethyl cellulose. The higher the degree of substitution, the higher the degree of carboxylation.
[0141] 2. Sensitive Zeta potential and particle size analyzer: After diluting the powder to 1% solid content, use 90Plus PALS to test the Zeta potential (surface charge). The surface charge can characterize the esterification degree of nano-sodium carboxymethyl cellulose. The more the surface charge, that is, the lower the surface charge value, the higher the esterification degree.
[0142] 3. Average length test: Add 0.02g of nano-sodium carboxymethyl cellulose into a 50mL clean beaker, add 20mL of deionized water, and use a 120W ultrasonic cleaner for 5 minutes to completely disperse the nano-sodium carboxymethyl cellulose in the deionized water to obtain the dispersion to be tested. Use a particle size analyzer (model: MasterSi zer 2000) to test the above dispersion to obtain the average length of the nano-sodium carboxymethyl cellulose.
[0143] 4. TEM test: The nano-sodium carboxymethyl cellulose prepared in Example 1 was subjected to TEM test, and its TEM image was obtained as follows: Figure 1 As shown in the figure, it can be seen that the nano-sodium carboxymethyl cellulose is linear.
[0144] 5. Crystallinity test: The PANaltical BV X-ray diffractometer produced by PANalytical of the Netherlands was used to perform X-ray diffraction analysis (XRD) on the phase structure of the materials prepared in this experiment. The crystallinity and other information of the material are obtained by the diffraction intensity and the shape of the diffraction peak, and the composition of the material is determined by comparing the obtained spectrum with the standard card. The test uses a copper target Kα, the wavelength of the ray is 0.154nm, the acceleration voltage is 40kV, the tube current is 30mA, the current scanning speed is 5℃ / min, and the scanning range is 10°-80°. The crystallinity (CI) of the sample is calculated according to the following formula: CI=IK / I0; where I0 represents the intensity of the highest diffraction peak, and IK represents the difference between the intensity of the highest diffraction peak and the intensity of the base plane of the diffraction peak.
[0145] 6. Strength test: The test is carried out using Yuanneng Technology's single particle mechanical properties testing system SPFT2000.
[0146] The above test results are listed in Table 2 below:
[0147] Table 2
[0148] Degree of substitution Surface charge (mV) Average length (nm) Crystallinity (%) Strength (Mpa) Example 1 1.2 -53 300 83.3 121.3 Example 2 1.1 -44 320 80.4 112.7 Example 3 1.2 -54 250 83.5 126.3 Example 4 1.2 -56 270 83.4 125.5 Comparative Example 8 1.2 -40 340 79.2 85.5 Comparative Example 9 0.8 -10 300000 63.2 12.3
[0149] According to the results in Table 2, the degree of substitution of the nano sodium carboxymethyl cellulose prepared in the embodiment of the present invention can reach 1-3, indicating that it has a high degree of carboxylation; the surface charge can reach -40~-60mV, indicating that it has a high degree of esterification. At the same time, its average length is 200-400nm, the crystallinity is 70%-90%, and the strength is 110-135Mpa.
[0150] In Comparative Example 8, the first catalyst 4-dimethylaminopyridine was not added, resulting in a decrease in the degree of esterification, an increase in the average length of the nano-sodium carboxymethyl cellulose, and a significant decrease in its strength; in Comparative Example 9, the second catalyst sulfuric acid was not added, resulting in a deterioration in the degree of esterification, crystallinity and strength, and the nano-sodium carboxymethyl cellulose could not be prepared.
[0151] Effect Example 2
[0152] The negative electrode slurries of Examples 5-12 and Comparative Examples 1-10 were subjected to the following tests:
[0153] 1. Viscosity test: After the negative electrode slurry is dispersed and stirred and after the negative electrode slurry is dispersed and stirred for 5 hours, the viscosity of the negative electrode slurry is tested in accordance with GB / T 1723-1993.
[0154] 2. Solid content test: at the end of the dispersion and stirring of the negative electrode slurry and after the dispersion and stirring of the negative electrode slurry is stopped for 5 hours, 10 ml of the upper negative electrode slurry, 10 ml of the middle negative electrode slurry and 10 ml of the lower negative electrode slurry are weighed from the upper layer (the position area of 90%-100% of the height of the stirring tank), the middle layer (the position area of 50%-60% of the height of the stirring tank) and the lower layer (the position area of 5%-10% of the height of the stirring tank) of the stirring tank, and they are recorded as the weight of the upper negative electrode slurry before evaporation, the weight of the middle negative electrode slurry before evaporation and the weight of the lower negative electrode slurry before evaporation; then they are weighed after evaporation and recorded as the weight of the negative electrode slurry after evaporation. The solid content is calculated as the weight of the negative electrode slurry after evaporation / the weight of the negative electrode slurry before evaporation. For example, the solid content of the upper negative electrode slurry is calculated as: the weight of the negative electrode slurry after evaporation / the weight of the upper negative electrode slurry before evaporation.
[0155] The above test results are listed in Table 3:
[0156] Table 3
[0157] Viscosity of negative electrode slurry at the end of dispersion stirring (cp) Solid content of the upper negative electrode slurry at the end of dispersion stirring (%) Solid content of the middle layer negative electrode slurry at the end of dispersion stirring (%) Solid content of the lower layer negative electrode slurry at the end of dispersion stirring (%) Viscosity of negative electrode slurry after 5h of stagnation (cp) Solid content of the upper negative electrode slurry after 5 hours of stagnation (%) Solid content of the middle layer negative electrode slurry after 5h of stagnation (%) Solid content of the lower negative electrode slurry after 5 hours of stagnation (%) Example 5 3653 39.9 40.1 40.2 4523 40.2 40.3 39.9 Example 6 3298 39.8 40 40.1 4169 40.1 39.8 40.3 Example 7 2874 40.1 40 40.2 3709 39.9 40.2 40.1 Example 8 2459 40.1 40.2 39.9 3254 40.1 40.2 39.9 Example 9 2139 39.8 40.4 40.2 2579 37.4 39.8 42.8 Example 10 3021 40.1 39.8 39.8 4020 40.2 40.6 39.8 Embodiment 11 3943 40.1 39.8 40.2 4892 40.3 39.8 40.1 Example 12 3784 40.3 40.2 40.5 4874 39.8 40.2 39.9 Comparative Example 1 2021 41 38 41 2563 35 39 46 Comparative Example 2 1954 36.7 43.2 41.3 2431 34 41 47 Comparative Example 3 1950 41.4 38.8 40.2 2354 33.5 42 48 Comparative Example 4 1893 40.2 35.4 43.2 2215 32 42 49 Comparative Example 5 2130 39 41 40 2454 38 40 43 Comparative Example 6 2569 40 39.9 40.1 3204 39.6 40 40 Comparative Example 7 2842 39.9 40.1 40 3567 40 39.8 40.1 Comparative Example 8 1121 38.7 40.3 45 1832 31.2 39.2 57.6 Comparative Example 9 121 12 21 84 132 8 9 93 Comparative Example 10 1893 40.3 38.9 43.2 2145 30.1 39.6 53.7
[0158] It can be seen from the data in Table 3 that the difference in solid content of the negative electrode slurry in the upper, middle and lower layers of the stirring tank of the embodiment of the present invention is small, indicating that the negative electrode slurry is highly uniform; the difference in viscosity of the negative electrode slurry before and after 5 hours of stagnation is small, indicating that the negative electrode slurry has good stability.
[0159] Effect Example 3
[0160] The following tests were performed on the negative electrode sheets of Examples 5-12 and Comparative Examples 1-10:
[0161] 1. Pole peeling force test: Tested in accordance with GB / T 25256-2010.
[0162] 2. Pole piece powder loss test: (pole piece-copper foil weight after peeling) / (pole piece-copper foil weight before peeling).
[0163] Half-cell preparation:
[0164] The electrolyte formula is: EC 20%, PC 20%, DEC 30%, PP 30%, LiPF6 15%, FEC 6%, PS2.5%, LiODFB 0.5%. The amount of electrolyte added to the button cell is about 0.5 ml, and the entire battery is assembled in a glove box to avoid contact with air.
[0165] Half-cell preparation: CR2450 button cell was used for testing, the positive electrode used a single negative electrode plate, the negative electrode used a lithium plate, and the voltage serial port used was (0-1.5V).
[0166] The following tests were performed on the half-cells prepared from the negative electrode sheets of the examples and comparative examples:
[0167] 1. Test of the expansion of the negative electrode sheet before and after the first lithium insertion: Expansion = (thickness of the negative electrode sheet before the first lithium insertion - thickness of the copper foil) / (thickness of the negative electrode sheet after the first lithium insertion - thickness of the copper foil).
[0168] 2. Resistivity of the unrolled electrode after drying at 1Mpa (Ω·m): At 1Mpa, place the test mold on the table of the electronic pressure tester and connect it to the resistivity tester. Increase the pressure of the electronic pressure tester to 1MPa, keep the pressure constant for 60s, then release the pressure to zero, read the sample deformation height and the value of the resistivity tester (the sample resistance). The conductivity is calculated according to the following formula σ=h / (S×R), where: σ is the powder conductivity of the negative electrode material layer, in S / cm; h is the sample deformation height, in cm; S is the sample bottom area, which is 3.14cm 2 ; R is the sample resistance, in Ω.
[0169] 3. 50% SOC expansion ratio test before and after battery failure for 1C cycle at 25°C (%): Taking 70% gram capacity as the benchmark, expansion ratio = (lithium-intercalated negative electrode sheet thickness at 50% gram capacity - copper foil thickness) / (lithium-intercalated negative electrode sheet thickness at 50% gram capacity of the first lithium-intercalated cycle - copper foil thickness).
[0170] 4. Cycle test: using Xinwei CT-4008Q-5V6A.
[0171] 1C cycle number (25℃): The number of cycles required to reach 70% of the gram capacity at a current intensity of 1C at 25℃.
[0172] 2C cycle number (25℃): The number of cycles required to reach 70% of the gram capacity at a current intensity of 2C at 25℃.
[0173] 3C cycle number (25℃): The number of cycles required to reach 70% of the gram capacity at a current intensity of 3C at 25℃.
[0174] 2C cycle retention rate (%): 2C cycles / 1C cycles at 25°C.
[0175] 3C cycle retention rate (%): 3C cycles / 1C cycles at 25°C.
[0176] The above test results are listed in Table 4 below:
[0177] Table 4
[0178] Pole peeling force (N / M) Powder loss of electrode (%) Expansion Resistivity (Ω·m) Expansion ratio (%) 1C cycle number 2C cycle number 3C cycle number 2C cycle retention rate (%) 3C cycle retention rate (%) Example 5 17.8 0.2 0.11 62.2 13.7 1298 1159 1107 89.3 85.3 Example 6 17.3 0.3 0.11 63.5 14.2 1259 1138 1103 90.4 87.6 Example 7 18.4 0.4 0.09 64.3 15.3 1237 1155 1105 93.4 89.3 Example 8 17.9 1.2 0.07 69.6 17.9 1233 1175 1163 95.3 94.3 Example 9 13.7 5.2 0.14 80.3 25.7 1134 909 841 80.2 74.2 Example 10 17.4 0.3 0.12 62.9 13.9 1273 1135 1087 89.2 85.4 Embodiment 11 17.8 0.2 0.11 63.2 13.9 1302 1164 1113 89.4 85.5 Example 12 17.6 0.2 0.11 63.3 13.8 1299 1165 1112 89.7 85.6 Comparative Example 1 7.5 1.3 0.15 94.2 27.1 519 443 85.4 426 82.1 Comparative Example 2 9.1 3.2 0.16 90.4 28 562 457 81.3 443 78.9 Comparative Example 3 13.4 4.5 0.17 88.8 28.5 617 483 78.3 463 75.1 Comparative Example 4 16.8 4.8 0.18 85.6 29.9 614 463 75.4 431 70.2 Comparative Example 5 14.7 3.2 0.14 83.3 25.6 943 800 84.8 759 80.5 Comparative Example 6 15.2 0.8 0.11 78.6 22.2 984 308 90.2 299 87.5 Comparative Example 7 3.7 8.9 0.19 77.5 34.7 342 717 80.2 628 70.2 Comparative Example 8 4.4 25.3 0.45 141.6 45.4 112 67 60.1 45 40.2 Comparative Example 9 0.1 90.1 0.76 193.2 0.78 12 1 9 1 9 Comparative Example 10 5.4 15.3 0.32 90.3 36.8 576 434 75.3 289 50.1
[0179] According to the data in Table 3, when the nano-sodium carboxymethyl cellulose prepared in the embodiment of the present invention is used in a battery, the number of 1C cycles of the battery can be more than 1134, the number of 2C cycles is more than 909, and the number of 3C cycles is more than 841, indicating that it has excellent cycle performance. At the same time, the 2C cycle retention rate of the battery is more than 80.2%, and the 3C cycle retention rate is more than 74.2%, indicating that it has excellent rate performance.
[0180] According to the results of Examples 5 to 9, when the mass of nano-sodium carboxymethyl cellulose in the negative electrode sheet accounts for 0.4%-1% of the mass of the active material layer, the peeling force of the negative electrode sheet can be further improved to above 17.3 N / M, and the resistivity of the negative electrode sheet can be further reduced to below 69.6 Ω·m. When the negative electrode sheet is used in a battery, the 1C cycle number of the battery can be further increased to above 1233 cycles, the 2C cycle number can be increased to above 1135 cycles, and the 3C cycle number can be increased to above 1087 cycles.
[0181] Comparative Examples 1-4 and 10 did not use sodium carboxymethyl cellulose in the pole pieces, and Comparative Examples 5-7 used commercially available sodium carboxymethyl cellulose, resulting in their 1C cycle numbers, 2C cycle numbers, and 3C cycle numbers being inferior to those in the examples.
[0182] Comparative Example 8 does not add the first catalyst 4-dimethylaminopyridine, and Comparative Example 9 does not add the second catalyst sulfuric acid, which results in a significant increase in the amount of electrode powder loss, expansion, and resistivity, and a significant decrease in the electrode peeling force. When used in a battery, the battery's cycle performance and rate performance both deteriorate.
[0183] Effect Example 4
[0184] The nano-sodium carboxymethyl cellulose prepared in Example 1 was characterized by TEM. The characterization results are as follows: Figure 1 As shown. Figure 1 It can be seen that the shape of the nano-sodium carboxymethyl cellulose crystal particles is linear.
Claims
1. A method for preparing nano carboxymethyl cellulose salt, characterized in that: It includes the following steps: The cellulose raw material and the mixture are reacted to obtain a precipitate; the precipitate is sequentially subjected to an alkalization treatment and an etherification treatment to obtain the nano carboxymethyl cellulose salt; wherein the mixture comprises a first catalyst and a second catalyst, the first catalyst is a catalyst having a function of catalyzing an esterification reaction, and the second catalyst is an acid solution.
2. The method for preparing nano carboxymethyl cellulose salt according to claim 1, characterized in that: The preparation method of the nano carboxymethyl cellulose salt meets one or more of the following conditions: (a) the cellulose raw material is one or more of wood, straw, pulp and cotton, preferably cotton; (b) the cellulose content in the cellulose raw material is 90% or more, preferably 95% or more, for example 99.5% or 99.9%; (c) the ash content of the cellulose raw material is less than 10%, preferably less than 5%, more preferably less than 0.1%, for example 0.1%; (d) the first catalyst comprises one or more of a pyridine compound, a pyrimidine compound and a pyrrole compound; Wherein, the pyridine compound is preferably 4-dimethylaminopyridine and / or 4-phenylaminopyridine, preferably 4-dimethylaminopyridine; (e) the acid solution is sulfuric acid and / or phosphoric acid, preferably sulfuric acid; Wherein, the mass concentration of the sulfuric acid is preferably 5%-15%, for example, 10%; (f) the mass ratio of the cellulose raw material to the first catalyst is (5-50):1, for example, 5:1, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1 or 45:1, preferably 20:1; (g) the mass ratio of the cellulose raw material to the second catalyst is 1:(1-50), for example, 1:5, 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40 or 1:45, preferably 1:10; (h) the reaction temperature is -20 to 100°C, for example, -20°C, 0°C, 5°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C or 100°C, preferably 60°C; (i) the reaction time is 1-10 h, preferably 2-9 h, for example 3 h, 4 h, 5 h, 6 h, 7 h or 8 h, more preferably 2-4 h, preferably 3 h; (j) the maximum particle size of the precipitate is preferably 0.1-2 μm, for example, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.8 μm, 1 μm, 1.2 μm, 1.4 μm, 1.6 μm or 1.8 μm; (k) after the reaction, further comprising the following steps to obtain a precipitate: adding deionized water to the product after the reaction, and separating the precipitate after standing; Wherein, the standing time is, for example, 24 hours; The separation is carried out by centrifugation, for example, wherein the centrifugal speed is, for example, 4000 r / min; (l) The pH value of the precipitate is 6-10, for example, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, preferably 7.
5.
3. The method for preparing nano carboxymethyl cellulose salt according to claim 1, characterized in that: The preparation method of the nano carboxymethyl cellulose salt meets one or more of the following conditions: (a) the alkalization step comprises: mixing an alkalizer and a dispersion containing precipitates for alkalization; Wherein, preferably, the alkalizing agent is sodium hydroxide; Preferably, the mass ratio of the precipitate to the alkalizing agent is (2-10):1, for example, 5:1; Wherein, after the alkalizing agent and the dispersion containing the precipitate are mixed, the pH value of the dispersion containing the precipitate is preferably 8-14, for example, 9, 10, 11, 12 or 13; The alkalization step preferably comprises: mixing the alkalizer, the dispersion containing the precipitate and ethanol and then performing alkalization; wherein the mass concentration of the ethanol is, for example, 75%; wherein the mass ratio of the alkalizer to the ethanol is, for example, 20:1, wherein the unit of mass is g and the unit of volume is L; Preferably, the temperature of the alkalization treatment is below 35°C, for example, 35°C; Preferably, the alkalization treatment time is 0.5-4h, for example, 1h, 2h or 3h; The method for preparing the dispersion containing the precipitate preferably comprises: mixing a dispersant and the precipitate to form the dispersion containing the precipitate; Preferably, the solid content of the dispersion containing the precipitate is 0.01%-20%, for example, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18% or 19%, for example, 5%; Wherein, the dispersant is preferably ethanol; Wherein, in the method for preparing the dispersion containing precipitate, the mixing includes a first mixing and a second mixing in sequence, and after the first mixing, in the dispersion containing precipitate, the mass ratio of the precipitate to the dispersant is 1:99; Wherein, the second mixing is preferably carried out by ultrasonic treatment; The ultrasonic treatment time is, for example, 30 minutes; Wherein, the ultrasonic treatment preferably adopts an ultrasonic cell pulverizer; Preferably, the ultrasonic treatment further includes centrifugal treatment; Wherein, the centrifugal speed of the centrifugal treatment is, for example, 14000 r / min; (b) the etherification treatment step comprises: mixing an etherifying agent and a treatment liquid containing a precipitate and heating the mixture to perform an etherification treatment; the treatment liquid containing a precipitate is obtained after the alkalization treatment; Preferably, the heating includes first heating and second heating in sequence, the temperature of the first heating is 40-70°C; the temperature of the second heating is 60-90°C; wherein the temperature of the first heating is, for example, 45°C, 50°C, 55°C, 60°C or 65°C; wherein the temperature of the second heating is, for example, 65°C, 70°C, 75°C, 80°C or 85°C; wherein the time of the first heating is preferably 30-60min, for example, 35min, 40min, 45min, 50min or 55min; wherein the time of the second heating is preferably 0.5-10h, for example, 1h, 1.5h, 2.0h or 5h; Wherein, the heating is, for example, water bath reflux heating; Preferably, the etherifying agent includes chloroacetic acid; preferably, the etherifying agent also includes ethanol; preferably, the mass content of chloroacetic acid in the etherifying agent is 20%-30%, for example, 26%; preferably, the mass ratio of the precipitate to the chloroacetic acid is 1:(0.05-0.1), for example, 1:0.057; (c) the etherification treatment further comprises a step of removing impurities; Wherein, the impurity removal is carried out by, for example, dialysis; Wherein, the molecular cutoff of the dialysis bag used in the dialysis is 8000-14000; (d) the pH value of the nano carboxymethyl cellulose salt is 7-8, for example, 7.7; (e) The nano carboxymethyl cellulose salt is nano carboxymethyl cellulose sodium.
4. A nano carboxymethyl cellulose salt obtained by the method for preparing the nano carboxymethyl cellulose salt according to any one of claims 1 to 3.
5. The nano carboxymethyl cellulose salt according to claim 4, characterized in that The nano carboxymethyl cellulose salt meets one or more of the following conditions: (a) The shape of the nano carboxymethyl cellulose salt crystal particles is linear; (b) the average length of the nano-carboxymethyl cellulose salt crystals is 200-400 nm, preferably 200-350 nm, for example 250 nm, 270 nm, 300 nm or 320 nm; (c) the surface charge of the nano carboxymethyl cellulose salt is -40 to -60 mV, for example, -56 mV, -54 mV, -53 mV or -44 mV; (d) the degree of substitution of the nano carboxymethyl cellulose salt is 1-3, for example, 1.1 or 1.2; (e) the crystallinity of the nano carboxymethyl cellulose salt is 70%-90%, for example, 80.4%, 83.3%, 83.4% or 83.5%; (f) the strength of the nano carboxymethyl cellulose salt is 110-135 MPa, for example, 112.7 MPa, 121.3 MPa, 125.5 MPa or 126.3 MPa; (g) The nano carboxymethyl cellulose salt is nano carboxymethyl cellulose sodium.
6. A binder, characterized in that: It comprises the nano carboxymethyl cellulose salt as claimed in claim 4 or 5.
7. The adhesive according to claim 6, characterized in that The binder meets one or more of the following conditions: (a) the mass percentage of the nano carboxymethyl cellulose salt to the mass percentage of the binder is 6%-25%, for example, 12%, 17% or 21%; (b) the binder further comprises polyacrylic acid and / or styrene-butadiene rubber; Preferably, the mass of the polyacrylic acid accounts for 60%-80% of the mass of the binder, for example, 63%, 66%, 69%, 74% or 78%; Preferably, the mass of the styrene-butadiene rubber accounts for 10%-20% of the mass of the adhesive, for example, 13%, 14%, 15% or 16%.
8. A pole piece, characterized in that: It comprises a current collector and an active material layer, wherein the active material layer comprises the binder according to claim 6 or 7.
9. The pole piece according to claim 8, characterized in that: The pole piece meets one or more of the following conditions: (a) The electrode is a negative electrode; (b) the mass of the binder accounts for 3%-4% of the mass of the active material layer, for example, 3.2%, 3.4%, 3.6% or 3.8%; (c) the mass percentage of the nano carboxymethyl cellulose salt to the mass percentage of the active material layer is 0.2%-1%, preferably 0.4%-1%, for example 0.6% or 0.8%; (d) the binder further comprises polyacrylic acid and / or styrene-butadiene rubber; Wherein, the mass of the polyacrylic acid accounts for 2%-3% of the mass of the active material layer, for example, 2.5%; Wherein, the mass of the styrene-butadiene rubber accounts for 0.2%-1% of the mass of the active material layer, for example, 0.5%; (e) the active material layer further comprises a negative electrode active material; Wherein, the negative electrode active material preferably includes one or more of conductive carbon black, carbon nanotubes, silicon-carbon material and conductive graphite; Preferably, the mass percentage of the negative electrode active material in the active material layer is 96%-97%, for example, 96.2%, 96.4%, 96.6% or 96.8%.
10. A battery, characterized in that: It comprises the pole piece as claimed in claim 8 or 9.